Biometry of infructescence, fruits and seeds of Mauritia flexuosa L. f. (Arecaceae) in veredas of the southern of Goiás (Research, Society and Development, 2022)
Given the ecological and economic importance of Mauritia flexuosa, the present work aimed to evaluate the biometric characteristics of infructescences, ripe fruits and seeds, as well as to compare whether there is variation in these data between the veredas and the zones of occurrence of the species in the Cerrado veredas. from the south of Goiás. Morphometric variables of 15 infrustescences and 750 buritis fruits collected in the border, middle and bottom zones of the paths were measured. The infructescences presented, on average, 614 fruits, length of 4.2 m and weight of 40 kg; 29, 5 rachillas with a length of 97.52 cm and 13.7% fruit production by infructescence. The fruits measured, on average, 47.84 mm in length, 41.23 mm in thickness, and weighed 52.43 g; the skin 8.6 g, the pulp 8.71 g and the endocarp 8.65 g. The seeds presented averages of 29.23 mm, 28.31 mm and 19.24 g for the respective measures of length, thickness and weight. Not all the morphometric measures evaluated showed differences between all the paths and between the edge, middle and bottom zones. These results possibly reflect both the different impacts that occurred in the veredas, as well as the homogenization of some of these areas by the same impacts, given that they are all surrounded by pasture and some have drains.